Operative behaviors. in open bile duct hydatid liver cyst (Q.A.V.B.): about 58 cases - Marella, Muzio S (Cirugía del Uruguay, 2020)
1) A nview of the opera ti ve technics utilized in 58 cases of hydatid cysts opened into the biliary tract ( H.C.O.B.T.) is presented. 2) The concept of H.C.O.B.T. is defined according to pathological criteria, considering as such all those cysts that have partially evacuated their contents into the biliary tract with no obstruction of tlie common bile duct. When this obstruction is present then the H.C.O.B.T. is considered both clinically and pathological ly as a biliohepatic disease. 3) The three. differents procedures available for the treatment of the H.C.O.B.T. are discussed: a) Cyst drainage. Hepatic monopolar operation. Minimal but fundamental procedure. b) Cyst drainage plus surgical exploration -and drainage- of the comm:on hile duct. Bipolar (complete) operation. e) Exploration and drainage of the common hile duct alone .. Biliary monopolar operation. This is an incomplete operation, not to be used as a rule, except under very special circunstances.